2005
DOI: 10.1002/art.21143
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies that bind glomeruli: Cross‐reactivity with bacterial antigen

Abstract: Objective. Systemic lupus erythematosus (SLE) is characterized by the production of multiple autoantibodies. Anti-DNA antibodies are associated with glomerulonephritis in SLE. It has been shown that anti-DNA antibodies cross-react with bacterial polysaccharide and, thus, might be elicited by microbial exposure. Non-DNA-binding antibodies also contribute significantly to the pathogenesis of lupus nephritis. The goal of this study was to characterize non-DNA-binding, kidneybinding antibodies.Methods. We generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…A first subpopulation would be associated with dsDNA, a second would be trapped by negatively charged molecules (the latter cross‐reacting with glomerular antigens), and a third would be sequestered by virtue of their genuine specificity for local antigens. The report that non–DNA‐binding antibodies recognize the same renal antigens as DNA‐binding antibodies (44) is compatible with our view that cross‐reactivity of anti‐dsDNA antibodies with kidney antigens determines their renal pathogenicity.…”
Section: Discussionsupporting
confidence: 86%
“…A first subpopulation would be associated with dsDNA, a second would be trapped by negatively charged molecules (the latter cross‐reacting with glomerular antigens), and a third would be sequestered by virtue of their genuine specificity for local antigens. The report that non–DNA‐binding antibodies recognize the same renal antigens as DNA‐binding antibodies (44) is compatible with our view that cross‐reactivity of anti‐dsDNA antibodies with kidney antigens determines their renal pathogenicity.…”
Section: Discussionsupporting
confidence: 86%
“…IgG antibodies to dsDNA used to be considered the most important antibody in SLE, especially with glomerulonephritis (54,55). However, in lupus patients, only 50% of antibodies eluted from glomeruli bound DNA (56). In our model, increased IgG deposition in glomeruli of apoE 2/2 Fas 2/2 mice with increased IgG anti-POVPC and anti-PGPC (Figs.…”
Section: Fasmentioning
confidence: 59%
“…Further investigations revealed that in total eight antibodies either reacting with pneumococcal saccharide or DNA were able to bind glomerular structures. Of these, six bound to renal protein antigens which had previously been described to be cross-reactive with DNA, whereas the remaining two bound to histones [ 76 ]. Effects of two additional bacteria could be shown more recently.…”
Section: Resultsmentioning
confidence: 99%